Effectiveness of improving coordination abilities after cardiac surgery: a review - Natalya V. Arkhipova; Svetlana A. Pomeshkina; Evgeniy V. Bykov (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. Bronchopulmonary complications remain the leading cause of postoperative morbidity and prolong the patient's hospital stay, increasing the cost of treatment. AIM. To study the effectiveness of using coordination training of the mechanics of respiratory movements in cardiac rehabilitation programs during breathing exercises. SEARCH STRATEGY. Through a literature search in the PubMed (Medline) and RISC search engines from January 2019 to December 2023, systematic reviews, meta-analyses and randomized controlled studies were selected of factors influencing the development of postoperative pulmonary complications after open heart surgery with cardiopulmonary bypass, as well as methods behavioral regulation and self-breathing training in cardiopulmonary rehabilitation to assess the effectiveness of reducing the number of pulmonary complications and their severity compared to conventional methods of respiratory cardiac rehabilitation. MAIN CONTENT. Based on an analysis of the literature, it has been suggested that after cardiac surgery, patients experience a decrease in coordination interactions in the work of the inspiratory muscles of the chest, which requires improvement in coordination abilities. The features of compensatory changes in the external respiration system after correction of the coordination interactions of the respiratory muscles in the process of respiratory-cardiac rehabilitation are illustrated, namely in increasing alveolar ventilation due to the improvement of the optimal ratios of thoracic and abdominal types of breathing, optimal synchronous and multiple ratios of the number of respiratory and motor cycles, its frequency and depth, higher efficiency of the respiratory muscles. CONCLUSION. The research results indicate that after completing a course of coordination training, where they developed the skills and abilities to control their breathing, patients who underwent open heart surgery with artificial circulation had a lower severity and incidence of postoperative bronchopulmonary complications, improved blood oxygen saturation and increased tolerance to physical activity compared to traditional methods of physical therapy, while the most pronounced changes are observed under the influence of methods of behavioral regulation of breathing. The obtained results of changes in the function of external respiration make it possible to evaluate the impact of coordination training to control one's breathing as beneficial for prevention and rehabilitation.